Evolusi Integrasi Pemasaran di Era Digital: Perbandingan Konseptual antara Integrated Marketing Communication dan Omnichannel Strategy - Jamira, Anaseputri (Fakultas Ekonomi dan Bisnis, 2026)
Digital transformation has reshaped how companies design and implement marketing strategies. Marketing activities are increasingly conducted through multiple interconnected channels such as social media, websites, mobile applications, marketplaces, and physical stores. This study aims to conceptually compare Integrated Marketing Communication (IMC) and Omnichannel Strategy as two approaches to marketing integration in the digital era. The research adopts a qualitative approach using a literature review of academic publications related to marketing communication, multichannel retailing, and customer experience. The findings indicate that IMC primarily emphasizes the consistency of marketing communication messages across different media, while Omnichannel Strategy focuses on integrating various channels and organizational systems to create a seamless customer experience. These findings highlight the evolution of marketing integration from communication coordination toward integrated customer experience management and provide a conceptual basis for future marketing research.